2013
DOI: 10.1016/j.jamcollsurg.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Robotic Surgery Warm-Up Improves Task Performance in a Dry Laboratory Environment: A Prospective Randomized Controlled Study

Abstract: Background Pre-operative simulation “warm-up” has been shown to improve performance and reduce errors in novice and experienced surgeons, yet existing studies have only investigated conventional laparoscopy. We hypothesized a brief virtual reality (VR) robotic warm-up would enhance robotic task performance and reduce errors. Study Design In a two-center randomized trial, fifty-one residents and experienced minimally invasive surgery faculty in General Surgery, Urology, and Gynecology underwent a validated ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 36 publications
0
77
2
4
Order By: Relevance
“…Two studies [22,25] reported a priori power calculations, but one of these studies [22] calculated that a substantially larger number of participants would be required than were actually recruited-thus indicating a lack of statistical power in this study. Relatedly, the sample sizes across all studies was generally modest, with only one RCT or cross-over study [25] reporting more than 20 participants per group. The included case studies could not be objectively assessed by the methods used to review the RCTs and cross-over studies, but each demonstrated methodological shortcomings, as discussed below.…”
Section: Assessment Of Biasmentioning
confidence: 98%
See 4 more Smart Citations
“…Two studies [22,25] reported a priori power calculations, but one of these studies [22] calculated that a substantially larger number of participants would be required than were actually recruited-thus indicating a lack of statistical power in this study. Relatedly, the sample sizes across all studies was generally modest, with only one RCT or cross-over study [25] reporting more than 20 participants per group. The included case studies could not be objectively assessed by the methods used to review the RCTs and cross-over studies, but each demonstrated methodological shortcomings, as discussed below.…”
Section: Assessment Of Biasmentioning
confidence: 98%
“…Only one study [25] was judged to be at low risk of bias: Table 1, 2. Five studies [22,23,25,26,29] were found to be at low risk of randomisation bias, with explicit detailing of the methods of randomisation and allocation concealment employed.…”
Section: Assessment Of Biasmentioning
confidence: 99%
See 3 more Smart Citations